Aptidão física, pico de velocidade de crescimento, composição corporal e o desempenho das habilidades técnicas de praticantes de futsal - Dahmer, Rodrigo (2019)
Indoor soccer requires its practitioner the improvement of physical fitness, a good performance of technical skills, in tandem with the circumstances of the game. Furthermore, the biological maturation and body composition stand out as elements that can distinguish the performance of athletes. Thus, the aim of this study was to analyze the relationship between the performance of technical skills and physical fitness, peak heigth velocity and body composition of under-13 indoor soccer practitioners in the Santa Maria Central-Urban region. The study group consisted of 40 male athletes with an average age of 12.62 years. The technical skills evaluated were controlling, driving, kicking and passing the ball. The elements of physical fitness evaluated were agility, speed, lower limb strength and also aerobic endurance. Peak height velocity and fat percentage were also evaluated. Data normality was performed using the Kolmorov-Smirnov test and for correlation analysis Pearson’s correlation was used. To evaluate the relative contributions of the indicators, multiple linear regression was resorted, using the Backward Stepwise Regression method to select the predictor variables, adopting the removal values of p <0.10 and a significance level of 0.05, using the SPSS 23. As a result, velocity was associated with agility (r = 0.831), lower limb strength (r = -0.789), ball conduction (r = 0.639), ball control (r = -0.613) and VO2max (r = -0.616). Agility was associated with Lower Limb Strength (r = -0.664) and ball control correlated with ball conduction (r = -0.753). It can be concluded that the elements of Physical Fitness are associated with the technical skills and also with the Body Fat Percentage, being the speed of fundamental importance for a better performance of the technical skills of controlling and driving the ball, as well as for better lower limb agility and strength performance in indoor soccer U-13 athletes.